PHASE SPACE METHODS FOR OPTICAL PROCESSING OF BIOMEDICAL INFORMATION. - Alieva, Tatiana (Revista Cubana de Física, 2005)
The application of optoelectronic techniques, based on Fourier transform, bilinear distributions, fractional transformations, for biomedical information processing: filtering, segmentation and classification of biomedical images, characterization of optical manipulators, recovering of statistical tissue properties, is discussed.